Wound healing in db/db mice with type 2 diabetes using non-contact exposure with an argon non-thermal atmospheric pressure plasma jet device - Arya Iswara; Kenta Tanaka; Tatsuo Ishijima; Yukari Nakajima; Kanae Mukai; Yasunori Tanaka; Yusuke Nakano; Junko Sugama; Makoto Oe; Mayumi Okuwa; Toshio Nakatani (PLoS ONE, 2022)
A non-thermal atmospheric pressure plasma jet (APPJ) may stimulate cells and tissues or result in cell death depending on the intensity of plasma at the target; therefore, we herein investigated the effects of non-thermal plasma under non-contact conditions on the healing of full-thickness wounds in diabetic mice (DM+ group) and normal mice (DM- group). A hydrogen peroxide colorimetric method and high performance liquid chromatography showed that APPJ produced low amounts of reactive oxygen and nitrogen species. Ten-week-old male C57BL/6j mice with normal blood glucose levels (DM- group) and 10-week-old male C57BLKS/J Iar-+Leprdb/+Leprdb mice (DM+ group) received two full-thickness cutaneous wounds (4 mm in diameter) on both sides of the dorsum. Wounds were treated with or without the plasma jet or argon gas for 1 minute and were then covered with a hydrocolloid dressing (Hydrocolloid), according to which mice were divided into the following groups: DM+Plasma, DM+Argon, DM+Hydrocolloid, DM-Plasma, DM-Argon, and DM-Hydrocolloid. Exudate weights, wound areas, and wound area ratios were recorded every day. Hematoxylin and eosin staining was performed to assess re-epithelialization and α-SMA immunohistological staining to evaluate the formation of new blood vessels. Non-thermal plasma under non-contact conditions reduced the production of exudate. Exudate weights were smaller in the DM+Plasma group than in the DM+Hydrocolloid and DM+Argon groups. The wound area ratio was smaller for plasma-treated wounds, and was also smaller in the DM+Plasma group than in the DM+Hydrocolloid and DM+Argon groups on days 1–21 (p<0.01). Wound areas were smaller in the DM-Plasma group than in the DM-Argon group until day 14 and differences were significant on days 1–5 (p<0.01). The percentage of re-epithelialization was significantly higher in the DM+Plasma group than in the DM+Argon and DM+Hydrocolloid groups (p<0.01). The number of new blood vessels that had formed by day 7 was significantly higher in the DM+Plasma group than in the DM+Hydrocolloid and DM+Argon groups (p<0.05). These results indicate that treatment with the current non-thermal plasma APPJ device under non-contact conditions accelerated wound healing in diabetic mice.